Analisis Teori Kuantum Dan Pengaruhnya Pada Teknnologi Modern - Zendrato, Krisman Jaya; Telaumbanua, Suci Mawarni (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Quantum theory is a fundamental branch of physics that explains phenomena at atomic and subatomic scales. This research explores the contributions of quantum theory to modern technological advancements, including quantum computing, quantum communication, and advanced materials. The study examines the core principles of quantum theory, such as superposition and entanglement, which underpin innovations across various fields. Findings reveal that quantum theory has significantly accelerated the development of revolutionary technologies, such as quantum computers and highly secure communication protocols. Despite challenges like scalability and environmental interference, quantum-based technologies hold immense potential to transform the future. This study highlights the need for interdisciplinary collaboration to overcome implementation barriers and maximize the benefits of quantum technologies in the era of Industry 4.0.